Desempenho de fibrocimentos extrudados produzidos com poupas celulósicas modificadas com silanos - Mendes, Rafael Farinassi (2014)
The objective of this study is to evaluate the physical-mechanical performance and the of fibercement composites produced with eucalyptus pulp surface-modified with different types of silanes at different concentrations and application methods. For the production of fibercement composites are used cellulose pulps bleached eucalyptus, obtained by the kraft process. The silanes used for surface funcionalization of the cellulose fibers pulp were isobutyltrimethoxysilane (IBTMS), methyltrimethoxysilane (MTMS) and noctyltriethoxysilane (OTES). The surface treatment of cellulose pulps is done in two ways, one by hydrolysis of the solution, with 10, 25 and 50% concentrations of application and another by direct application of the product in cellulose pulp with 25% concentration of application. After the composites production, these had their physical and mechanical properties evaluated after 28 days of curing and after 200 and 400 cycles aging. The results it can be concluded that: 1) The three types of silanes (MTMS, IBTMS And OTES) were efficient in the chemical modification of the cellulose pulps, providing lower mean values of moisture absorption, 2) The 25 and 50% concentrations of silanes showed the best results modification; 3) The treatment with cellulose pulps modified by direct application of the IBTMS and MTMS silanes prevented extruding the mixture; 4) The composites produced with the modified pulps by OTES and IBTMS silanes, applied via hydrolysis, showed the best results for water absorption, apparent porosity and shrinkage properties when tested after 28 days of curing and after 200 and 400 cycles accelerated aging; 5) After accelerated aging, chemical modifications of the pulps, regardless of the type of silane and application form, caused significant increase in MOR, MOE and LOP properties; 6) The three types of silanes used allowed the improvement and maintenance of the mechanical performance of the fibercement after 200 and 400 cycles accelerated aging; and 7) The combination of hydrophilic pulp with the extrusion process, using low water-cement ratio and shows high densification and consequently better fiber-matrix relation, allows to obtain a product with good mechanical properties for a longer period of time.